Keanekaragaman Jenis Vegetasi Riparian pada Daerah Hulu dan Hilir Sungai Noemuti Kabupaten Timor Tengah Utara - Messah, Vinsensia Yosefa; Binsasi, Remigius; Binsasi, Yeremias; Bani, Polikarpia Wilhelmina (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Riparian ecosystem is a transition zone between land and water bodies that plays an important role in maintaining environmental balance, preventing erosion, filtering pollutants, and providing habitat for biodiversity. This study aims to analyze the diversity of riparian vegetation types in the upstream and downstream of the Noemuti River. The method used is the plot method with a size of 20m x 20m with a total of 24 plots. The results of the analysis showed that there were significant differences in the composition and structure of riparian vegetation between the upstream and downstream of the Noemuti River. In the upstream area, 31 plant species were found belonging to 20 families with a total of 751 individuals, while in the downstream 23 species were found from 16 families with a total of 831 individuals. Dominant species in the upstream include Tectona grandis (262 individuals), Senna siamea (66 individuals), and Leucaena leucocephala (53 individuals), while in the downstream it is dominated by Gliricidia sepium (309 individuals), Vachellia nilotica (131 individuals), and Tectona grandis (125 individuals). The highest Importance Value Index (IVI) in the upstream was shown by Tectona grandis, each of 80.88% (tree), 116.43% (pole), 63.94% (sapling), and 37.57% (seedling). In the downstream, Gliricidia sepium became the most dominant species with IVI of 66.02% (tree), 108.62% (pole), 63.48% (sapling), and 46.05% (seedling). The invasive species Chromolaena odorata also showed significant dominance in the seedling strata with an INP of 39.98% in the upstream and 59.00% in the downstream. The Shannon-Wiener diversity index (Hʹ) in the upstream was recorded at 2.42 and in the downstream at 2.05, both of which are included in the moderate diversity category. The species richness index (R) was higher in the upstream (4.38) compared to the downstream (3.25), while the evenness index (E) was recorded at 0.70 in the upstream and 0.65 in the downstream.